2021
DOI: 10.3390/coatings11070748
|View full text |Cite
|
Sign up to set email alerts
|

Based on Ultrathin PEDOT:PSS/c-Ge Solar Cells Design and Their Photoelectric Performance

Abstract: In recent years, nanostructures have improved the performance of solar cells and are regarded as the most promising microstructures. The optical properties of PEDOT:PSS/c-Ge hybrid solar cells (HSCs) based on the octagon germanium nanoparticles (O-GNPs) were numerically analyzed using the finite-difference time-domain (FDTD) method. The optimal structure of the hybrid solar cell is determined by changing the thickness of the organic layer and structural parameters of nanoparticles to enhance the optical absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…It can be clearly found that the extinction intensity of the two peaks decreases with the increase of the polarization angle. At the same time, we also noticed that when the incident plane wave is TE polarization, two new resonance peaks appear, which are caused by phase resonance (Qin et al, 2020;Su et al, 2021). The electric field generated at this time has a phase difference of π, which causes the far field to produce coherent cancellation, thereby generating two new peaks.…”
Section: Resultsmentioning
confidence: 68%
“…It can be clearly found that the extinction intensity of the two peaks decreases with the increase of the polarization angle. At the same time, we also noticed that when the incident plane wave is TE polarization, two new resonance peaks appear, which are caused by phase resonance (Qin et al, 2020;Su et al, 2021). The electric field generated at this time has a phase difference of π, which causes the far field to produce coherent cancellation, thereby generating two new peaks.…”
Section: Resultsmentioning
confidence: 68%
“…The efficient application of clean energy is the focus of current research. Among them, the application of solar energy is particularly critical [1][2][3]. As a clean energy, solar energy is widely used in many fields, such as photocatalysis, solar cells and so on [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The research on broadband absorber has been carried out for many years in the world, and it has been used in solar cells, solar heating devices and photothermal converters (Liu et al, 2017;Keshavarz and Vafapour, 2019;Yu et al, 2020;Chen et al, 2021c;Su et al, 2021). For the design and improvement of broadband absorber, we should pay attention to the following aspects: the first is to select the appropriate material.…”
Section: Introductionmentioning
confidence: 99%